2012
DOI: 10.1371/journal.pone.0043595
|View full text |Cite
|
Sign up to set email alerts
|

Biosignatures for Parkinson’s Disease and Atypical Parkinsonian Disorders Patients

Abstract: Diagnosis of Parkinson’ disease (PD) carries a high misdiagnosis rate due to failure to recognize atypical parkinsonian disorders (APD). Usually by the time of diagnosis greater than 60% of the neurons in the substantia nigra are dead. Therefore, early detection would be beneficial so that therapeutic intervention may be initiated early in the disease process. We used splice variant-specific microarrays to identify mRNAs whose expression is altered in peripheral blood of early-stage PD patients compared to hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
92
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(96 citation statements)
references
References 72 publications
4
92
0
Order By: Relevance
“…In particular, changes in mRNA from cellular whole blood can facilitate the identification of dysregulated processes and diagnostic biomarkers for PD (1,2). Several molecular signatures in blood have been identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, changes in mRNA from cellular whole blood can facilitate the identification of dysregulated processes and diagnostic biomarkers for PD (1,2). Several molecular signatures in blood have been identified.…”
mentioning
confidence: 99%
“…For example, 22 unique genes were found differentially expressed in blood of PD patients compared with healthy controls (1). Likewise, specific splice variants in blood were associated with PD in samples obtained from two independent clinical trials (2,3). In addition, altered expression of the vitamin D receptor (VDR) in blood and reduced plasma levels of 25-hydroxy vitamin D 3 have been associated with PD (1,4).…”
mentioning
confidence: 99%
“…For example, mutations in APP linked to familial Alzheimer's disease increase the extracellular concentration of amyloid b protein (Ab) in vivo [31]. More recently, cerebrospinal fluid (CSF) concentrations of Ab peptides have been widely used to study Alzheimer's disease pathology in vivo and their utility to diagnose Parkinson's disease with dementia is under evaluation [32]. In addition to Alzheimer's disease, other neurological disorders including Down's syndrome, autism, and epilepsy are characterized by elevated expression of APP [33].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to what the authors suggest, we are cognizant that several markers will be required to accurately identify earlystage PD patients. Our previous studies identified several markers, most of which were replicated in two independent clinical trials (3,4). It is our view that a combination of RNA and biochemical markers in blood and cerebrospinal fluid, for example, will be required for accurate diagnosis.…”
mentioning
confidence: 90%